Legal Aspects of Telemedicine and Prevention of Malpractice Risks - Nasution, Fatihana; Aji Lukman Ibrahim (Universitas Brawijaya, 2024)
This study aims to determine the practice of implementing telemedicine in Indonesia and examine the legal formulation of telemedicine implementation to prevent malpractice risks to patients. The study employs a normative juridical method with a statutory and conceptual approach. Secondary data is utilised, including primary (legislation), secondary (literature reviews), and tertiary legal materials (dictionaries) relevant to telemedicine and its legal implications. The findings reveal that Indonesia currently lacks specific regulations governing telemedicine. The existing Health Minister Regulation Number 20 of 2019 is inadequate to comprehensively guide telemedicine practices in the country. As a result, the implementation of telemedicine carries significant legal risks. Based on established principles of medical practice, telemedicine poses malpractice risks because doctors do not physically examine patients. Furthermore, the current regulations fail to address the primary aspects of telemedicine comprehensively, exacerbating the risk of malpractice and creating legal uncertainty when malpractice occurs. To address these issues, it is crucial to develop specific telemedicine regulations. These regulations should define the doctor-patient relationship, outline the rights and obligations of all parties, ensure the protection of electronic medical records, establish criminal sanctions for violations, and create an independent supervisory body to oversee telemedicine practices.